Instability mechanism of water-wading soft rock slope during storage period in Fushun west open-pit mine - Jihuan WU; Guanhong DONG; Xuguang LI; Shan JIANG; Tianyu MA; Yuan CUI (Shuiwen dizhi gongcheng dizhi, 2025)
The Fushun west open pit mine, encompassing over 12 km2, with a maximum depth exceeding 400 m, has undergone more than a century of intensive mining. While the mine has significantly contributed to regional development, it has also led to serious geological safety concerns, particularly slope deformation and instability. Following mine closure, a strategy of “water storage into lakes” for the treatment of the mine pit has been proposed. To prevent the occurrence of subsequent geological disaster events, this study investigated the mechanism of unstable landslide of soft rock slope during storage period in mining area through detailed geological survey, geotechnical test, and numerical simulation techniques. The results shows that pit water storage has four effects on soft rock slope: soft rock weakening, hydrostatic pressure on the toe of slope, floating weight reduction, and seepage force in slope according to influence degree. Soft rock weakening is the main cause of instability of water-wading slope. Under the same intensity of “filling and storage” transformation, the stability of the middle section of the soft rock slope is the lowest. For instance, when the pit is filled to −150 m and then water is stored to −50 m, the east and west sections of the soft rock slope are basically stable, while the middle section is unstable and prone to cutting through mudstone and shale to cause landslides. The potential sliding mass is about 133.4×104 m3. It is suggested that during the reconstruction process, special attention should be paid to water-proofing and seepage prevention measures for the rock mass, as well as reinforcing measures at the slope toe in the middle section of the slope. This study provide technical guidance for the repair and treatment of Fushun West open-pit mine and similar deep open-pit mines.